Small dense LDL and its Association with Hypertension: a Case-Control Study (Bangladesh Journal of Medical Biochemistry, 2013)
Hypertension is one of the most common diseases affecting humans throughout the world. The commonest variety of hypertension is benign essential hypertension. Cardiovascular risk is more in hypertensive patients as their lipid profile is more atherogenic than normotensive subjects. Traditionally, estimation of total serum cholesterol and LDL-C are used as an indicator of atherogenicity. But subjects may develop hypertension and CHD with normal levels of LDL cholesterol. So assessment of LDL cholesterol concentration may not entirely reflect its atherogenic potential. Because LDL-C is not a single entity rather it consists of seven distinct subclasses of different particle size. The size of the LDL particle is inversely correlated to their atherogenicity. Smaller LDL particles are more atherogenic despite their less cholesterol content than the larger more buoyant LDL particles containing more cholesterol. Therefore individuals having smaller LDL particles are more atherogenic and more at risk to develop hypertension inspite of even normal LDL cholesterol concentration. So measurement of small dense LDL particle is more important than any other lipid measure. With this aim 122 subjects were included in this study, among them 82 were diagnosed cases of essential hypertension with the mean age of 42.56±9.98 years and 40 were healthy controls. Serum apo-B was measured in all study subjects. The amount of apoB is almost similar in every LDL subtypes but the amount of cholesterol increases with the increasing particle size. So the ratio of cholesterol to apo-B decreases as the particle size decreases, thus LDL cholesterol / apo-B £ 1 indicates the presence of atherogenic small dense LDL. So the prevalence of small dense LDL was evaluated by calculating the ratio of LDL-C/apo B. The ratio was significantly lower in hypertensive cases (0.093±0.18) compared to controls, indicating presence of sd LDL in hypertensive patients. When the risk ratio was calculated, the patients having small dense LDL in their plasma were found to have 2.87 times more risk for developing CVD then the persons who doesn't have small dense LDL in their plasma. DOI: http://dx.doi.org/10.3329/bjmb.v5i1.13427 Bangladesh J Med Biochem 2012; 5(1): 20-23